Five Facts on Non-Compete and Related Clauses in OECD Countries - Dan Andrews; Andrea Garnero (Institute of Labor Economics (IZA), 2025)
Restraints clauses that prevent workers from joining (or starting) a competing firm (non-compete clauses), the disclosure of confidential information or the poaching of former co-workers or clients are traditionally justified to protect legitimate business interests (e.g. trade secrets, investments in training). Yet, there are increasing concerns that such clauses may be deployed to suppress job mobility and competition. This paper reviews the international evidence base and finds that non-compete clauses are more prevalent than anticipated, with up to one-quarter of employees subject to such clauses in some countries. These clauses extend beyond highly paid professionals to include low-wage and elementary workers, often bundled with other restrictions, further diminishing workers' bargaining power. The balance of evidence suggests that non-compete clauses suppress job mobility, firm entry, innovation, wages and productivity, which more than offset any gains from enhanced incentives for firm-specific investment. Regulatory efforts to limit non-compete clauses are gaining traction in some countries but comprehensive empirical evidence remains scarce outside the United States, underscoring the need for more research.
Keywords: J31; J41; J42; L40; 330; non-compete clauses; monopsony; earnings; knowledge diffusion; mobility